1993
DOI: 10.1016/0735-1097(93)90579-p
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Placebo-Controlled Study of Ibopamine and Diagoxin in Patients With Mild to Moderate Heart Failure: Results of the Dutch of the Ibopamine Multicenter Trial (DIMT)

Abstract: Ibopamine and digoxin both inhibit neurohumoral activation in patients with mild to moderate chronic heart failure. However, the clinical effects of these drugs are different and appear to be related to the degree of left ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(64 citation statements)
references
References 28 publications
3
57
2
2
Order By: Relevance
“…By contrast, the Dutch ibopamine multicentre trial suggested that digoxin exerted clinical benefits even in patients with moderate heart failure who were treated only with diuretics. 55 Two recent studies in patients with mild to moderate heart failure and sinus rhythm indicate that such patients also tend to deteriorate after abrupt withdrawal of digitalis.68 69 The RADIANCE study is particularly noteworthy in this respect, as all patients in this study, in contrast to previous investigations with digitalis, were taking ACE inhibitors69 (fig 6). Thus, when clinical efficacy is concerned, it makes sense to give digitalis to patients with comparatively severe heart failure and sinus rhythm despite the accepted standard treatment of diuretics and ACE inhibitors.…”
Section: Glycosidescontrasting
confidence: 51%
“…By contrast, the Dutch ibopamine multicentre trial suggested that digoxin exerted clinical benefits even in patients with moderate heart failure who were treated only with diuretics. 55 Two recent studies in patients with mild to moderate heart failure and sinus rhythm indicate that such patients also tend to deteriorate after abrupt withdrawal of digitalis.68 69 The RADIANCE study is particularly noteworthy in this respect, as all patients in this study, in contrast to previous investigations with digitalis, were taking ACE inhibitors69 (fig 6). Thus, when clinical efficacy is concerned, it makes sense to give digitalis to patients with comparatively severe heart failure and sinus rhythm despite the accepted standard treatment of diuretics and ACE inhibitors.…”
Section: Glycosidescontrasting
confidence: 51%
“…5 Previous studies showed that in patients with heart failure, ibopamine reduced plasma concentrations of noradrenaline, renin activity, and aldosterone. [6][7][8] Clinical studies have reported that ibopamine improves symptoms and has an effect similar to captopril on exercise tolerance in patients with mild-tomoderate heart failure. 9,10 Ibopamine seemed to be a new class of drug that might make an important contribution to the management of patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Вторым объяснением положительных эффектов дигоксина при ХСН может служить его способность даже в небольших дозировках снижать активность САС [75,76] и даже РААС [77].…”
Section: возможности контроля чсс у пациентов с хсн и синусовым ритмомunclassified